AN ECONOMIC ORDER QUANTITY MODEL FOR AMELIORATING ITEMS WITH QUADRATIC DEMAND - Mamuda, Mamuda Alhaji; Ali, Uba Ahmad; Usman, Abubakar Umar; Musa, Jibrin Yahaya (FUDMA Journal of Sciences, 2025)
It is evidently recognized that in a real life, the volume of stocked items has motivational effect on customers. Stores with large amount of displayed items attract buyers more than stores with scanty items. The EOQ model for Quadratic Demand items that undergo amelioration stage was developed. The poultry, fishery, and so on, where the stocked item increases in weight and/or value within a shortest period of time. The model determines the best cycle length so as to minimize the overall cost. Numerical examples are given to illustrate the model and a sensitivity analysis carried out to see the effect of changes to some model parameters on the decision variables.
Keywords: Economic Order Quantity; Amelioration; Quadratic Demand